Cultural and creative networks as enabling contexts for artistic research - Gemma Grau Pérez (European Journal of Cultural Management and Policy)
Cultural and creative networks serve as essential environments that could foster innovation and advancement within artistic research practice. This study investigates how formal networks contribute to strengthening transdisciplinary collaboration, interdisciplinary dialogue, and societal impact of artistic research. Leveraging grounded theory principles, the research delves into the ways in which these networks can provide fertile ground for exploring novel artistic research pathways across ontological, epistemological, and methodological dimensions. Through the analysis of key categories and themes emerging from the empirical research, this study highlights the role of formal networks in the cultural and creative sector, particularly in addressing discipline-specific challenges and unlocking the full potential of artistic inquiry. By shedding light on the mechanisms through which networks facilitate the production and dissemination of knowledge, this study offers insights into the evolving landscape of artistic research and its broader societal impacts. The practical implications of the findings for practitioners, policymakers, and artistic stakeholders are examined. Ultimately, the findings underscore the significance of leveraging cultural and creative networks as drivers of transformative advancements within the artistic research community.